MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN ASURANCE, RELEVANCE, INTEREST, ASSESMENT, SATISFACTION - Putri Sri Mahyuni Lubis; Fitriani Fitriani; Nur Sahara (Journal of Didactic Mathematics, 2020)
The problem in this study is the low ability of students to solve mathematical problems. To solve this problem, the researchers used the ARIAS model. As for the purpose of this study is to improve students' mathematical problem-solving abilities, increase student activity, improve teacher teaching abilities through the ARIAS learning model. This type of research is classroom action research. The results of the research the problem-solving ability of the first cycle was 56% and 88% in the second cycle increased by 32%. The level of student activity towards mathematics increased, this was obtained by a percentage of 62% in cycle I, and 85% in cycle II increased by 23%. The teacher's ability to manage to learn was 56% in cycle I and 94% in cycle II, with an increase of 38%. The author concluded that students 'mathematical problem-solving abilities, student learning activities, and teachers' ability to manage learning increased in class X MIA-1 SMA Negeri 1 Padang Bolak.